GEOPOLITICAL ANALYSIS OF THE SIGNIFICANCE OF THE SOUTH CAUCASUS FOR INTERESTS OF TURKEY (British Journal of Global Ecology and Sustainable Development, 2024)
This research work delves into the evolving dynamics of Georgia's role in shaping Turkey's foreign policy strategies. The study seeks to understand the multifaceted dimensions of the bilateral relationship between Turkey and Georgia, particularly exploring the factors that have influenced the evolving role of Georgia in Turkey's foreign policy calculus. Through a comprehensive analysis of diplomatic, economic, and security dimensions, the research uncovers the intersecting interests and mutual dependencies that have led to a deepening of ties between the two countries. Special attention is given to the strategic significance of the South Caucasus and the Black Sea region in anchoring Turkey's foreign policy objectives and the role that Georgia plays in this context. Additionally, the study assesses the impact of regional developments, including energy security, infrastructure projects, and geopolitical alignments, on shaping Turkey's approach towards Georgia. Insights gained from this research contribute to a nuanced understanding of the intricate linkages between Georgia's regional significance and Turkey's broader foreign policy framework, ultimately shedding light on the complexities of contemporary geopolitical dynamics and regional cooperation initiatives.